EFFECT OF MASTITIS ON MILK COMPOSITION OF CROSS-BRED (HOLSTEIN FRIESIAN X CHOLISTANI) AND SAHIWAL CATTLE - T. Ahmad; A. Ghafoor; M. Nadeem; M. Q. Bilal; A. Sharif (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2023)
The present study was designed to investigate the effect of mastitis on various components including fat percentage, protein, total solids, solid not fat, pH, specific gravity and lactose content in milk of cross-bred (Holstein Friesian × Cholistani) and Sahiwal cattle. A total of 376 milk samples (excluding blind and nonfunctional teats) from 100 cows (50 cross-bred and 50 sahiwal) were collected aseptically. Animals of different ages, parity and stages of lactation were selected under field condition. The diagnosis of subclinical mastitis was done on basis of Surf Field Mastitis Test. For bacterial examination of milk, the samples were grown in laboratory and various biochemical tests were performed. The results of the present study indicated that solid not fat (SNF) of mastitic sahiwal and cross-bred cattle and total solids percentage of normal and mastitic cattle were significantly reduced as the severity of mastitis increased in animals. The milk pH of normal and mastitic cattle including both sahiwal and cross-bred was significantly increased in severe cases of mastitis. The specific gravity of normal and mastitic milk samples showed that there was no significant difference in specific gravity as compared to normal. The protein percentage of normal and mastitic cattle including both sahiwal and cross-bred cattle indicated that protein concentration was significantly reduced in severe cases of mastitic animals. The findings of present study highlighted that mastitis cause major alterations in composition of milk leading to poor quality of the milk.